Rural routes and networks creating and preserving routes that are sustainable, convenient, tranquil, attractive and safe. (Thomas Telford, 2002)
This report invites people to take a fresh view of how the countryside is changing, to use their judgement, and to ensure that the future we build is one we want, not the one we could have avoided.